Invisi Guard: Blockchain-Powered Invisible Code Technology for Anti-Counterfeit Assurance - Jeenath Laila N; Mohamed Rizwan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Counterfeit products are a major concern for businesses and consumers alike, as they can lead to significant financial losses and damage to brand reputation. To combat this problem, a blockchain-based system using Invisible Quick Response(QR) codes has been proposed.This paper focuses on a novel approach for storing invisible QR code images using the InterPlanetary File System (IPFS) and recording the Content Identifier (CID) in a blockchain system to enhance counterfeit avoidance in e-commerce websites. Traditional QR codes are visible and can be easily replicated, making them susceptible to counterfeiting. By utilizing invisible QR codes, the proposed method adds an extra layer of security. The IPFS is employed as a decentralized storage system, allowing the QR code image to be securely stored and accessed. The CID, a unique identifier for the stored image, is then recorded in a blockchain, providing an immutable and transparent record of the QR code's authenticity. Additionally, a name server and Access Control List (ACL) are implemented to facilitate efficient retrieval of QR code information while maintaining security and privacy. This approach enhances trust and authenticity in e-commerce transactions by enabling buyers to validate the legitimacy of products through the blockchain-recorded CID associated with the invisible QR code. The proposed system provides an effective solution to mitigate counterfeiting and build consumer confidence in online purchase.